How do children prepare to react?: imaging maturation of motor preparation and stimulus anticipation by late contingent negative variation - Bender, Stephan; Weisbrod, Matthias; Bornfleth, Harald; Resch, Franz; Oelkers-Ax, Rieke (NeuroImage, 2005)
Both the motor system and the frontal executive control system show a late maturation in humans which continues into school-age and even adolescence. We investigated the maturation of preparation processes towards a fast motor reaction in 74 healthy right-handed children aged 6 to 18 years and analyzed the topography of the late component of contingent negative variation (lCNV) in a 64-electrode high density sensor array. While adolescents from about 12 years on showed a bilaterally distributed centro-parietal maximum like adults do, younger children almost completely missed the negativity over the left central area contralaterally to the side of the anticipated movement. The reason, as revealed by current source density, was that only adolescents showed significant evoked activity of the left pre-/primary motor and supplementary/cingulate motor areas, while in contrast both age groups displayed significant current sinks over the right (ipsilateral) centro-temporal area and right posterior parietal cortex. Spatio-temporal source analysis confirmed that negativity over the right posterior parietal area could not be explained by a projection via volume conduction from frontal areas involved in motor preparation but represented an independent component with a different maturational course most likely related to sensory attention. Significant event-related desynchronization of alpha-power over the contralateral sensorimotor cortex was found in the younger age group, indicating that also 6- to 11-year-old children were engaged in motor preparation. Thus, the missing current sink over the contalateral sensorimotor cortex during late CNV in 6- to 11-year-old children might reflect the immaturity of a specific subcomponent of the motor preparation system which is related to evoked (late CNV) but not induced activity (alpha-ERD).
Gesehen am 16.12.2021